Kinerja Grafik X-Bar menggunakan Variabel Parameter dan Double Sampling dengan Pendekatan Rantai Markov - Wardatus Syarifah (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2021)
X-bar control chart is one of the means used to resolve problems or detect specific causes that might occur in the production process. When using charts X-bar, there are situations where the average process can diverge. If the average process of the irregularities, it takes a complex approach involving Markov chains to evaluate the properties of graphs X-bar. In this research discusses the performance of the graph X-bar using Variable Parameters and Double Sampling with Markov chain approach. Stages used is determine the state Variables Parameters and Double Sampling, making a transition matrix for Variable Parameter and Double Sampling, determining Average Time of Cycle and Average Time to Signal, comparison test, conclusions and suggestions. By comparing Variables Parameters and Double Sampling obtained a good method to use for a particular situation on the graph X-bar, that is when a small sample size using Variable Parameters and when a large sample size using Double sampling.